MEDICAL AND PEDAGOGICAL NAVIGATION AND FORMATION OF THE REHABILITATION OF THE CULTURE OF FAMILIES UPBRINGING CHILDREN WITH HEALTH PROBLEMS - Светлана Николаевна Викжанович; Ольга Юрьевна Синевич; Татьяна Юрьевна Четверикова (The Publishing House Medicine and Enlightenment, 2019)
The article reports on the peculiarities of medical and pedagogical navigation of families raising children with disabilities. Families of this type are considered as a special social group due to the emotional experience of a difficult life situation associated with the child's disease. On the medical and pedagogical Advisory point example which functions in the structure of Omsk state pedagogical University, the organizational and substantial aspects of specialist's activity with the goal of creating a rehabilitation culture of families in every aspect: axiological, cognitive, praxeological are displayed. The requests of parents for the maintenance of specialized assistance from pediatricians and defectologists teachers are studied and illustrated by examples. There are 4 stages of activity with parents, professional specialist's strategies on each of them are displayed.